Service Quality, Awareness, And Knowledge Of Taxpayers On Compliance With Land And Building Tax Payments With Tax Sanctions As A Moderating Variable - Torang Simatupang; Thezar Fiqih Hidayat Hasibuan; Sari Nuzullina Rahmadhani (Publikasi Indonesia, 2023)
This study aims to determine the impact, Service Quality, Taxpayer Awareness, Tax Knowledge, and Tax Sanctions on Taxpayer Compliance. This study took a sample of taxpayers in Jati Kesuma Village, Namo Rambe District, which were taken randomly. The number of samples taken was 88 people. This study also uses the variable tax sanctions as a moderating variable. The data analysis method used in this research is Moderated Regression Analysis (MRA) using SPSS for Windows. So the results of this study indicate that taxpayer awareness, service quality, and tax knowledge have a positive and significant influence on taxpayer compliance. The tax sanction variable acts as a pure moderator that strengthens the relationship between the dependent variable and the independent variable.